2002
DOI: 10.1002/rem.10052
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ion‐exchange (IX) technology and biological reduction for perchlorate removal

Abstract: Ion-exchange (IX) resin is perhaps the most promising INTRODUCTIONIn the southwestern United States, perchlorate (ClO 4 -) contamination has been detected in waters and soils near facilities that manufactured or utilized sodium, potassium, and ammonium perchlorate salts.The concentration of this contaminant varies depending on the site; with many measurements in the parts per million (ppm) range in locations where perchlorate was manufactured (Boralessa, 2001). In other sites, where perchlorate contamination i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Large amounts of AP and other explosive‐related compounds have been released at locations where rocket fuel is produced, refurbished, maintained and disposed, or at sites where rockets are tested and fired. Consequently, perchlorate has been detected in a variety of drinking water resources, both ground and surface water, particularly in the south‐western US (Schumacher 1960; Batista et al. 2002; Hogue 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Large amounts of AP and other explosive‐related compounds have been released at locations where rocket fuel is produced, refurbished, maintained and disposed, or at sites where rockets are tested and fired. Consequently, perchlorate has been detected in a variety of drinking water resources, both ground and surface water, particularly in the south‐western US (Schumacher 1960; Batista et al. 2002; Hogue 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Though the ion-exchange resin system is considered to be a promising technology for removing perchlorate from waterbodies, it is just a separation mechanism where wastewater solutions containing perchlorate after ion-exchange treatments need further treatment. To overcome this drawback, Batista et al ( 2002 ) proposed a technology combining ion-exchange and biological reduction for perchlorate removal. Woodberry et al ( 2007 ) conducted a fi eld trial (see Table 4 ) at Thala Valley tip, Casey Station, Antartica, and found that iminodiacetic acid chelating ion-exchange resins could help in reducing 92-100 % of heavy metals in the following order of selectivity: Cd ∼ Zn > Ni ∼ Cu > Fe within 1 year of treatment.…”
Section: Adsorptionmentioning
confidence: 99%
“…The bifunctional ion-exchange resin bed treated nearly 40,000 empty bed volumes of groundwater, and about 100 % perchlorate was successfully removed in 6 months. To overcome this drawback, Batista et al ( 2002 ) proposed a technology combining ion-exchange and biological reduction for perchlorate removal. Bifunctional anion-exchange resin (Purolite A530E) and FeCl 3 -HCl (as the resin generation system) were used for the full-scale study.…”
Section: Ion-exchangementioning
confidence: 99%